2020
DOI: 10.25248/reaenf.e5220.2020
|View full text |Cite
|
Sign up to set email alerts
|

A importância do tempo para o clampeamento do cordão umbilical para o recém-nascido: uma revisão integrativa da literatura

Abstract: Esse artigo buscou analisar o impacto e a importância do tempo do clampeamento do cordão umbilical para o recém-nascido. Tratou-se de uma revisão integrativa da literatura realizada na plataforma eletrônica Biblioteca Virtual em Saúde (BVS) que compõem as bases de dados: PubMed, Lilacs, Scielo e Medline. Após a análise da amostra observou-se abordagens distintas em relação ao momento adequado para clampeamento do cordão umbilical, no entanto 60% dos estudos evidenciaram diversos benefícios do clampeamento tard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Research investigating the clinical practices of umbilical cord clamping through interviews with professionals reiterate this fact, since they show that professionals, for the most part, are aware of the proper way to perform the procedure (18)(19) . Existing knowledge, however, is not reflected in daily practice (20) and in the data found in studies evaluating clinical practice, which still show low rates of delayed/optimal clamping (10,(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research investigating the clinical practices of umbilical cord clamping through interviews with professionals reiterate this fact, since they show that professionals, for the most part, are aware of the proper way to perform the procedure (18)(19) . Existing knowledge, however, is not reflected in daily practice (20) and in the data found in studies evaluating clinical practice, which still show low rates of delayed/optimal clamping (10,(16)(17) .…”
Section: Discussionmentioning
confidence: 99%
“…A study evaluating the factors associated with umbilical cord clamping in a large hospital in Nepal showed that the newborns who underwent any intervention following delivery were less likely to undergo delayed/optimal umbilical cord clamping when compared to those who received no intervention (17) . Possibly this is because when the newborn requires special support for stabilization, clamping is performed quickly for the child to be taken to the care required (20) . However, there are safe recommendations that it is possible to perform resuscitation maneuvers with the newborn close to the mother and with the umbilical cord still intact (21)(22)(23) .…”
Section: Discussionmentioning
confidence: 99%
“…A equipe de enfermagem foi uma das principais responsáveis em possibilitar esse contato precoce entre mãe e filho. Ademais, o ato de pinçar o cordão imediatamente após o nascimento resulta numa redução de 20% no volume de sangue para o neonato e uma redução de mais de 50% no volume de glóbulos vermelhos, sendo os bebês que tem o clampeamento imediato ao nascer apresentam maiores chances de anemia no primeiro ano de vida (Ruivo et al, 2020). A prática do clampeamento oportuno esteve presente em várias falas maternas, sinalizando a sensibilidade das parturientes para a tal prática na experiência de parto no CPN; Em contrapartida, na categoria seguinte sobre experiências de parto anteriores, o clampeamento imediato e a prioridade de intervenções predominam e se opõe às experiências vivenciadas no CPN.…”
Section: Discussionunclassified